(untitled) (Global Journal of Management and Business Research, 2012)
In this paper the analysis has been done in the aspect of studies on job satisfaction: a case study of engineers India limited, A excel public Sector Company of India. Many qualitative aspects have been asked in the survey and there is one thing that now a day employees do not give importance to mere fiscal requirement but also to working environment which include many work related and non-work related aspects those have been asked in the survey. With the generation of more and more money in the market and work pressure on individual has been tantamount due to which employees seek for comfort in work and many things which may help alleviate work pressure and so their personal / social tension. During recession, when other organizations were issuing pink slips, Engineers India Limited recruited most due its demand in the market. Except some differences in few question asked in survey, in general majority seems to have similar opinion and agrees to the importance of good working culture inclusive of aspects which treats them more than a machine.